La negociación colectiva en el Perú: la hiperdescentralización y sus múltiples inconvenientes - Villavicencio Ríos, Alfredo (2015)
In Latin America, most countries have a decentralized bargainingstructure that is in the company’s main area of negotiation and different from the warranty obligations and promotion deriving from the new Latin American constitutionalism emerged after the fall of dictatorships in the last quarter of the past century. In Peru, the legislative option enforces a hyper- decentralized model that has restricted maximum coverage and effectiveness of the collective protection. Therefore, the state regulation referred to the articulated collective bargaining is not complete because it ignores issues such as the legal nature of the instruments of juncture, the framework agreements, their effectiveness, etc.The weakness of the collective protection has transcended the specific field of business and questions the social, economic and political balances that underpin the constitutional rule of law.